Clinical outcomes in patients with advanced epidermal growth factor receptor‐mutated non‐small‐cell lung cancer in South Western Sydney Local Health District. Issue 12 (10th December 2017) - Ding, Pei N.; Roberts, Tara L.; Chua, Wei; Becker, Therese M.; Descallar, Joseph; Yip, Po Y.; Bray, Victoria
Abstract: Background: Epidermal growth factor receptor (EGFR)‐mutated non‐small‐cell lung cancer (NSCLC) is a subgroup of oncogene addicted lung cancer that predicts response to tyrosine kinase inhibitors (TKI). However, there is variability in response and survival outcomes in patients with EGFR mutation treated with TKI. Aim: To describe clinical characteristics, treatment patterns and factors influencing outcomes in patients with EGFR‐mutated NSCLC in South Western Sydney Local Health District. Methods: Retrospective review of patients with EGFR‐mutated NSCLC diagnosed between January 2010 and June 2016. Results: A total of 85 EGFR‐mutated NSCLC patients was identified; 80 (94%) received first‐line treatment with EGFR‐TKI. The median follow‐up was 10.7 months with a median duration of treatment of 9 months. On disease progression ( n = 44), 37% had best supportive care only, 30% received chemotherapy, 23% participated in clinical trials, 7% continued on a first generation EGFR‐TKI and 3% received afatinib. Overall response rate to first‐line EGFR‐TKI was 66%. Median progression‐free survival (PFS) was 10.7 months (range 2.7–55.9 months) and median overall survival (OS) was 23 months (range 0.4–35.8 months). Multivariate Cox regression analysis showed that patients with lower disease burden (<4 sites) had longer PFS (hazard ratio (HR) 0.36, 95% confidence interval (CI) 0.18–0.72, P = 0.004) but not OS. Good performance status predicts longer OS (HR 0.33, CI 0.14–0.77, P = 0.01). Lower (<5) pre‐treatment neutrophil‐to‐lymphocyte ratio (NLR) was associated with better PFS (HR 0.40, 95% CI 0.18–0.87, P = 0.02) and OS (HR 0.43, 95% CI 0.19–0.94, P = 0.04). There were no survival differences when patients were stratified by age, baseline albumin level and types of EGFR mutation. Conclusion: Results from this community‐based cohort confirm known prognostic factors in patients with EGFR‐mutated NSCLC receiving TKI and suggest the negative influence of a heightened host systemic inflammatory response on patient outcomes.